Conservative Management in a Ventilated Preterm Neonate with Pneumopericardium, Pleural Effusion, and Pulmonary Collapse: A Case Report - Yazdan Ghandi; Niloofar alsadat Motamedi (Mashhad University of Medical Sciences, 2018)
Background: Neonatal pneumopericardium (PPC) is a rare clinical condition usually associated with other air leak syndromes. It increases morbidity and mortality due to cardiac tamponade. Case report: A preterm male neonate weighing 1260 g was born with the gestational age of 28 weeks. Cardiopulmonary resuscitation was routinely performed without any medical therapy. The newborn was transferred to the neonatal intensive care unit due to marked respiratory distress with tachypnea and cyanosis. Pulse oximetry showed oxygen saturation of 70%. A whiteout of the lung and air-bronchogram pattern was found on the chest X-ray. The arterial blood gases demonstrated PH=7.14, PCo2=51 mmHg, Po2=36 mmHg, bicarbonate=15.8 mg. The neonate was intubated with a tracheal tube size 2.5 and mechanical ventilation was initiated with 90% fraction of inspired oxygen (FiO2), PIP=14 cmH2O, and PEEP=4 cmH2O. After intubation, the newborn received two doses of surfactant. On the third day, patent ductus arteriosus was established and appropriate treatment was performed. After five days, the chest X-ray was repeated due to increasing respiratory distress and an increasing FiO2, which revealed a pneumopericardium with right-sided pleural effusion and left upper lobe collapse. Afterwards, pleurocentesis was performed. Left ventricular ejection fraction (65%) was preserved and no evidence of cardiac tamponade was observed. Serial chest X-ray and echocardiography were performed daily. After the next seven days, the chest radiograph demonstrated a complete resolution of the pneumopericardium, pleural effusion, and lung collapse. Conclusion: The present case study presented a preterm neonate suffering from pneumopericardium along with pleural effusion and lung collapse. Despite the complexity, the PPC was asymptomatic and eventually resolved without pericardiocentesis.